Inner boundary value problem with displacement for a second order mixed parabolic-hyperbolic equation - Balkizov, Zh.A.; Guchaeva, Z.Kh.; Kodzokov, A.Kh. (Bulletin of the Karaganda University. Mathematics Series, 2022)
This paper investigates inner boundary value problems with a shift for a second-order mixed-hyperbolic equation consisting of a wave operator in one part of the domain and a degenerate hyperbolic operator of the first kind in the other part. We find sufficient conditions for the given functions to ensure the existence of a unique regular solution to the problems under study. In some special cases, solutions are obtained explicitly.